Mismatch repair deficiency associated with complete remission to combination programmed cell death ligand immune therapy in a patient with sporadic urothelial carcinoma: immunotheranostic considerations. Issue 1 (December 2015) - Castro, Michael; Goldstein, Neal
Abstract Background Mismatch repair deficiency (MMRD) is a common pathway of malignant transformation accounting for approximately 15–20 % of human carcinogensis. It has been postulated that MMRD increases tumor antigenicity and highlights a role for immunotherapeutic approach MMR-deficient cancers. This strategy was pursued in a patient with upper tract urothelial carcinoma, and the results are reported here. Case Presentation Molecular profiling was performed using next generation DNA sequencing and (IHC) testing for MMR and PD-L1. A patient with sporadic, high grade urothelial carcinoma of the renal pelvis was found to have a hypermutator genotype with 73 mutations occurring amidst 62 known drivers of malignancy, and 340 VUS alterations. MMR deficiency phenotype was confirmed by the absence of MSH2 and MSH6 as well as deleterious mutations in these genes. IHC staining for programmed cell death ligand-1 [PD-L1] revealed 2+ staining in 80 % of cells. The patient gained access to combination immunotherapy trial utilizing MEDI4736 and MEDI0680 through a clinical trial. The patient achieved a prolonged, complete remission within two months and had no severe ill effects from the treatment. Conclusion Given their ability to generate neo-antigens, MMR-deficient cancers may be uniquely susceptible to immune checkpoint inhibitor strategies, including urothelial tract cancers. Screening for MMR deficient cancers has the potential to become a routine strategy for evaluating the role of PD-L1 inhibitors for patient with advanced disease. (Trial registration: Clinicaltrials.gov NCT00938834. Registered 13 July 2009)